Evaluation of the effects of losartan on a random pattern skin flap model in rats - (:unkn) unknown (TURKISH ASSOC TRAUMA EMERGENCY SURGERY, 2011)
BACKGROUND Losartan, a drug with antiinflammatory properties, has been shown to prevent ischemic injury in various organs. The purpose of the present study was to investigate the effects of losartan on ischemic skin flaps and on flap survival. METHODS A 3x9 cm dorsal flap was elevated in 24 Sprague-Dawley rats. Rats received the following treatment for seven days: Group I (n = 8): 10 mg/kg losartan; Group II (n = 8): 40 mg/ kg losartan; and Group III (n = 8): nonionized water. At the end of the seventh day, the viable flap areas were calculated, and histological analysis was conducted to count cells and capillaries in microscopic fields. RESULTS Mean flap survival was 61%, 56% and 60% in Groups I, II and III, respectively. Comparison of flap survival between groups did not yield any significant difference (p > 0.05). Ischemic zones of the flaps in all groups demonstrated an increase in number of neutrophils, fibroblasts and capillaries (p < 0.05), whereas no difference was seen in mast cells. The cell counts in the viable areas of the flaps showed a significant decrease in fibroblasts in the group treated with 40 mg/kg losartan (p < 0.05). The number of neutrophils, mast cells and capillaries was not influenced by treatment. CONCLUSION Losartan does not improve skin flap survival but it has a significant antiproliferative effect on fibroblasts.
Keywords: Angiotensin; AT1; fibroblast; flap survival; ischemic flap; ischemia- reperfusion; losartan; reperfusion injury; MYOCARDIAL-ISCHEMIA-REPERFUSION; NITRIC-OXIDE SYNTHASE; ANGIOTENSIN-II; SURVIVAL RATES; RECEPTOR; INJURY; INHIBITION; EXPRESSION; PROTECTION; INCREASE